Possible bias from rating behavior when subjects rate both exposure and outcome - Toomingas, Allan; Alfredsson, Lars; Kilbom, Åsa (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'In many epidemiologic studies the subjects rate both the exposure and the outcome, assigning numerical values to the variables according to their perceptions and judgments. Hypothetically, subjects who tend to overestimate, exaggerate, or use high numerical values in rating tasks would rate both exposure and outcome higher than subjects who tend to underestimate, dissimulate, or use low numerical values. A range of such rating behaviors among the subjects would introduce uncontrollable bias to relative risk estimates, in most cases an overestimation. The aim of this study was to assess the possible presence of and effects on relative risk estimates of such high and low rating behavior among subjects in an epidemiologic study of musculoskeletal disorders.' ' METHODS ': 'Rating behavior was analyzed by intercorrelating the ratings of 19 different stimuli. High positive correlations would indicate the presence of high and low rating behavior.' ' RESULTS ': 'The correlations were, however, both positive and negative and close to zero. Adjusting for rating behavior did not affect relative risk estimates, based on subjective ratings of both exposure and outcome.' ' CONCLUSION ': 'There is no support in this study for the existence of a range of high and low rating behavior among subjects who rate neutral and nonaffective stimuli, such as time, weight, number and physical exposure, as well as pain and other symptoms. There is therefore no support for the idea of a bias to relative risk estimates from such rating behavior in studies where subjects rate both exposure and outcome variables of this kind.
Keywords: individual differences; judgment; method; response style; risk assessment; validity